2012
DOI: 10.4194/1303-2712-v12_1_15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was designed to describe the occurence of external abnormalities in Black Sea flounder (Platichthys flesus luscus) reared in captivity. In the present study, a total of 2187 juvenile fish were examined. Eight hundred eighty eight Platichthys flesus luscus had one or more of the following conditions: reversed (sinistral), malpigmentation, malformed jaw, incomplete eye migration. Average total length and body weight of abnormal juveniles were significantly lower than that of normal juveniles (P < 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…At the understanding level, the student's haves be able to organize and interpret what they have learned, it means that they can visualize and express it in a different way using their own words each piece of information given to them [9]. Although there is a difference in the way of expressing the information in the process of understanding, the content of the information has to follow its scientific rule.…”
Section: Conceptual Changementioning
confidence: 99%
See 3 more Smart Citations
“…At the understanding level, the student's haves be able to organize and interpret what they have learned, it means that they can visualize and express it in a different way using their own words each piece of information given to them [9]. Although there is a difference in the way of expressing the information in the process of understanding, the content of the information has to follow its scientific rule.…”
Section: Conceptual Changementioning
confidence: 99%
“…From the result, it is indicated that CCT structure is superior in improving concept understanding and misconception reduction. CCT is more effective than conventional text in restructuring the students' schemata that undergo misconceptions [5,9,13]. The effectiveness of CCT because of its advantages that gives the chance to the students to construct concepts through cognitive conflicts which occur in learning.…”
Section: Effect Of Text Structure On Understanding and Misconception mentioning
confidence: 99%
See 2 more Smart Citations